2012
DOI: 10.1167/iovs.12-9477
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Recessive Retinitis Pigmentosa Due ToABCA4Mutations: Clinical, Pathologic, and Molecular Characterization

Abstract: The persistence of transcripts expressed by inner retinal neurons suggests that despite significant plasticity that occurs during retinal degeneration, bipolar cells and ganglion cells remain at least partially differentiated. Findings from this study suggest that some forms of therapy currently under investigation may have benefit even in advanced retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…A substantial contribution of primary photoreceptor loss in nullizygous patients is consistent with the postmortem evaluation of a human donor eye harboring two likely null mutations (p.F1440fs and c.2160þ1G>C), which at 78 years of age revealed loss of the outer nuclear layer over the whole retina with regional preservation of the RPE. 34 That the cones were relatively more endangered compared to rods was suggested by studies on a ABCA4 À/À / Nrl À/À mouse model, which indicated that ABCA4-deficient cones simultaneously generate more A2E than rods and are less able to effectively clear it. 33 The advantage of a genotype-phenotype correlation study using strict genetic inclusion criteria is the capacity to discover the range of phenotypes associated with a specific genotype.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial contribution of primary photoreceptor loss in nullizygous patients is consistent with the postmortem evaluation of a human donor eye harboring two likely null mutations (p.F1440fs and c.2160þ1G>C), which at 78 years of age revealed loss of the outer nuclear layer over the whole retina with regional preservation of the RPE. 34 That the cones were relatively more endangered compared to rods was suggested by studies on a ABCA4 À/À / Nrl À/À mouse model, which indicated that ABCA4-deficient cones simultaneously generate more A2E than rods and are less able to effectively clear it. 33 The advantage of a genotype-phenotype correlation study using strict genetic inclusion criteria is the capacity to discover the range of phenotypes associated with a specific genotype.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 It has also been proposed that direct photoreceptor cell death may precede RPE alterations. 42,43 Given the fact that cGMP is an important retinal player in general, and also in RP at least when PDE6A and PDE6B mutations are concerned, clinical measurements of cGMP levels in ocular tissue or in body fluids in various retinal states are few. In the context of retinal detachment, La Heij et al 44 have shown reduced cGMP levels in vitreous as well as subretinal fluid in patients with detached retinas, compared to control samples, and similar results have been obtained in experimental retinal detachments in pigs.…”
Section: Purposementioning
confidence: 99%
“…Degeneration of the CC is commonly observed in human models of RP, although its immediate cause is unknown (Li et al, 1995;Milam et al, 1998;Mullins et al, 2012). The CC is usually absent from areas in which photoreceptors have completely degenerated and in which RPE cells have migrated away from the CC, towards the retinal capillary layers (Li et al, 1995;Milam et al, 1998), suggesting that the loss of photoreceptors and RPE is either directly or indirectly responsible for CC degeneration (see Roberts, 2015, for a detailed discussion).…”
Section: Introductionmentioning
confidence: 99%